Micro Controller Modeling On Digital FX Pedal For Guitar And Bass Using Arduino Pro Micro - Bastyan, Hanafi Dana; Utami, Putri Febi (Universitas Amikom Purwokerto, 2024)
A musician, especially a guitarist or a bassist, is certainly familiar with digital sounds or tones. Almost in the current technological era, they also use technology in music. Currently, there are many digital music devices. One of them is the use of digital effects for guitars and basses. These devices very widely, from large to compact. Sometimes guitarists and bassists often have difficulty controlling them. This is because the design of the device is made minimalist, so that with the large number of preset tones available with a small number of controls, it will complicate their performance on stage. The use of digital effects requires a large storage capacity, therefore, the role of the digital effect is like a processor in the CPU. If so much storage is not controlled, then it is possible to forget the configuration settings. Therefore, control is needed as a support and a tool to remind the preset memory. Therefore, additional devices are needed to control the preset tones. This paper will discuss how to create a model to control preset tones in the digital effects they use. The goal is to make it easier when they perform on stage. With good control features, and the arrangement of the appropriate tone arrangement, guitarists and bassists will find it easy to manage the presets stored in the digital effect memory.